Geo-Congress 2022 Advances in Monitoring and Sensing; Embankments, Slopes, and Dams; Pavements; and Geo-Education. - Lemnitzer, Anne; Stuedlein, Armin Wilhelm, 1978- (GSP (Series), 2022)
GSP 336 contains 56 peer-reviewed papers on monitoring and sensing and embankments, slopes, and dams presented at Geo-Congress 2022, held in Charlotte, North Carolina, March 20-23, 2022.